(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article presents one of the unique healthy Kyrgyz drinks koumiss and ways to promote tourists for the treatment of health by drinking the national drink koumiss. Each country has its own peculiarities of national drinks.